Gender inequality in a globalizing world - Stephanie Seguino (Levy Economics Institute of Bard College, 2005)
Emphasis on market-friendly macroeconomic and development strategies in recent years has resulted in deleterious effects on growth and well-being, and has done little to promote greater gender equality. This paper argues that the example of East Asia states, which recognized their position as late industrializers, relied on a managed-market approach with the state that employed a wide variety of policy instruments to promote industrialization. Nevertheless, while Asian growth was rapid, it was not enough to produce greater gender equality. A concentration of women in mobile export industries that face severe competition from other low-wage countries reduces their bargaining power and inhibits closure of gender-wage gaps. Gender-equitable macroeconomic and development policies are thus required, including financial market regulation, regulation of trade and investment flows, and gender-sensitive public sector spending.
Keywords: L5; O1; F4; E24; F16; J16; I31; 330; gender; inequality; industrial policy; firm mobility; trade